2001
DOI: 10.1007/s1012601-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

Channel Catfish Follicle-Stimulating Hormone and Luteinizing Hormone: Complementary DNA Cloning and Expression During Ovulation

Abstract: Gonadotropins are important regulators of reproduction. To develop molecular resources for production of recombinant gonadotropins, we have cloned and sequenced complementary DNA encoding the channel catfish (Ictalurus punctatus) follicle-stimulating hormone (FSH) and luteinizing hormone (LH), which encode 132 and 140 amino acid proteins, respectively. The deduced amino acid sequences of the catfish FSH and LH are highly conserved with those cloned from other teleosts. Both the FSH and the LH were highly induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…Since duality of GtHs has been reported widely from primitive teleosts (Kajimura et al 2001b;Kato et al 1993;Liu et al 2001;Suzuki et al 1988a;Swanson et al 1991;Van Der Kraak et al 1992;Yoshida et al 2001;Yoshiura et al 1997Yoshiura et al ,1999 to advanced teleosts (Copeland and Thomas 1993;Elizur et al 1996;García-Hernández et al 1997;Hassin et al 1995;Jackson et al 1999;Kajimura et al 2001a;Koide et al 1993;Lin et al 1992;Mateos et al 2003;Okada et al 1994;Tanaka et al 1993), the absence of antiFh FSHβ 50-60 positive cells is probably caused by lack of immunoreactivity from lower similarities in the antigen region (the amino acid sequences of the region have 36-55% similarity between the mummichog and primitive teleosts of Elopomorpha, Ostariophysi, and Protacanthopterygii; Table 4). …”
Section: Discussionmentioning
confidence: 99%
“…Since duality of GtHs has been reported widely from primitive teleosts (Kajimura et al 2001b;Kato et al 1993;Liu et al 2001;Suzuki et al 1988a;Swanson et al 1991;Van Der Kraak et al 1992;Yoshida et al 2001;Yoshiura et al 1997Yoshiura et al ,1999 to advanced teleosts (Copeland and Thomas 1993;Elizur et al 1996;García-Hernández et al 1997;Hassin et al 1995;Jackson et al 1999;Kajimura et al 2001a;Koide et al 1993;Lin et al 1992;Mateos et al 2003;Okada et al 1994;Tanaka et al 1993), the absence of antiFh FSHβ 50-60 positive cells is probably caused by lack of immunoreactivity from lower similarities in the antigen region (the amino acid sequences of the region have 36-55% similarity between the mummichog and primitive teleosts of Elopomorpha, Ostariophysi, and Protacanthopterygii; Table 4). …”
Section: Discussionmentioning
confidence: 99%
“…Using such an approach, we have characterized a complete set of all 32 small ribosomal protein cDNAs [7] and a complete set of all 47 large ribosomal protein cDNAs [30] from channel catfish. Other genes we have analysed include: the myostatin gene [10]; gonadotropin (GnRH) α-subunit [17]; GnRH β-subunit 1 and GnRH β-subunit 2 [15]; the α-actin gene [8]; the creatine kinase gene [16]; a number of cytokine genes; a number of complement genes; and a large number of cytochrome P450 genes (Liu, unpublished).…”
Section: Systematic Characterization Of Genes And/or Full Length Cdnasmentioning
confidence: 99%
“…As shown in Figs 1 and 2, the E. japonicus LH β subunit has typical structural characteristics of fish LH β subunit such as 12 cysteines, one N‐linked glycosylation site and the conserved short amino acid sequences, which are important for heterodimerization, stability and metabolic fate of GTHs (Ulloa‐Aguirre et al , 1999; Liu et al , 2001). Power et al (1997) reported that C. pallasii LH β also has these characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…As in terrestrial vertebrates, two types of GTH (GTH‐I and GTH‐II) have been identified in many representative groups of the teleost lineage such as Salmonidae (Itoh et al , 1988; Suzuki et al , 1988 a ; Sekine et al , 1989; Kato et al , 1993), Anguilliformes (Yoshiura et al , 1999; Kajimura et al , 2001 a ; Han et al , 2003), Cypriniformes (Chang et al , 1988, 1990; Yoshiura et al , 1997; So et al , 2005), Siluriformes (Rebers et al , 1997; Liu et al , 2001; Vischer et al , 2003), Perciformes (Copeland & Thomas, 1993; Hassin et al , 1995; Elizur et al , 1996; Rosenfeld et al , 1997; Jackson et al , 1999; Mateos et al , 2003), Pleuronectiformes (Kajimura et al , 2001 b ; Cerdà et al , 2008), Gasterosteiformes (Hellqvist et al , 2004) and Cyprinodontiformes (Lin et al , 1992; Shimizu & Yamashita, 2002). To date, the comparative and phylogenetic studies on fish GTHs have provided lines of evidence that fish GTH‐I and GTH‐II are homologues of vertebrate FSH and LH, respectively (Querat et al , 2000).…”
Section: Introductionmentioning
confidence: 99%